Yesterday, Today and Forever - 5 Year Anniversary - Anastasiou, Spyros; Bachlitzanaki, Irini; Batchelor, David J.; Beraud, Raymonde; Braithwaite, Angus; Christodoulides, Savvas; Colclough, Gary; Gregoriou, Theodoulos; Doukanaris, Panayiotis; Kalisperas, Ramon; Marathaki, Eva; Münster, Jost; et al. (My University, 2020)
Art Seen is delighted to announce the group exhibition titled Yesterday, Today and Forever curated by Maria Stathi. This exhibition is to mark the five years celebration of the gallery and highlights sixteen of the collaborative artists as well as 4 guest artists. Participating artists: Spyros Anastasiou (CY), Irini Bachlitzanaki (GR), David J Batchelor (UK), Raymonde Beraud (CY), Angus Braithwaite (UK), Savvas Christodoulides (CY), Gary Colclough (UK), Theodoulos Gregoriou (CY), Panayiotis Doukanaris (CY), Ramon Kalisperas (CY), Eva Marathaki (GR), Jost Münster (DE), Vicky Pericleous (CY), Mary Plant (CY), Amy Stephens (UK), Lefteris Tapas (CY), Diana Taylor (UK), Maria Theodoraki (GR), Amikam Toren (IL) and Alison Turnbull (UK). For the past five years, the curatorial line of the owner Maria Stathi, aims at the promotion and projection of the art scene in Nicosia by presenting important solo and group exhibitions. Art Seen focuses and expands on curatorial and art practices that investigate modes of contemporary making and exhibiting. Art Seen curates, displays and promotes work of both local and international artists, in a wide range of approaches and mediums. Nonetheless these works contribute to an imaginative critical language of art making and thinking today. Now more than ever, Art Seen remains committed to its founding ideals for supporting and promoting contemporary creation and providing an open space for contemporary art while pushing the boundaries. The artist Diana Taylor responds to the curatorial idea of the exhibition and develops the following reasoning: "What is it about this time that we live in that so compels us to reflect inwards upon our present and how it is defined? We live in a time of the ‘re’: of re-assembling, re-contextualising and re-appropriating images repeatedly, reinterpreting their meanings- one picture reposted over the last. In considering our contemporary condition, we can understand that what prevails is the paradoxical sense of not being fully in the now, or with time as the word directly translates, rather there exist multiple and constantly shifting temporalities, layered one upon another. Contemporaneity sees the end of a linear understanding of art history; rather it is punctuated by a sense of anachronism, poly-temporality and contradiction: of being here, now, then and there at the same time. It is not surprising then, that in an age of rapidly advancing technologies and mass consumption, our gaze also remains in the rear view mirror, looking back to sensibilities of the past and to material traditions. Simultaneously then we are deconstructing the past, negotiating a push/pull of things and times both coming together and falling apart- yesterday, today and forever. Yesterday, Today and Forever surveys this notion of contemporaneity whilst celebrating the five year history of Art Seen contemporary and artists who have exhibited at the gallery since it opened." Art Seen organisation was founded in 2015 by curator Maria Stathi, as an opportunity to expand on cultural exchanges and synergies within the cultural scene of Cyprus and beyond. Previously she was the director of Anthony Reynolds Gallery, in the West End in London, for over five years and of Omikron Gallery, Nicosia. In the last decade she has curated more than 19 solo and 16 group exhibitions of both leading and emerging artists.